The Influence of Social Media and Influencers in Increasing Branding of Pelita Bangsa Student Business - Muhamad, Mamad; Santoso, Trisno Aji; Hardiansyah, Hardiansyah; Ramadhani, Yunita; Wiyatno, Tri Ngudi (LPPPIPublishing, 2025)
Study This aiming For analyze social media influence and influencers towards business branding enhancement student University Lamp Nation . In the digital era, social media No only become means communication , but Also transform become tool effective marketing for perpetrator business micro , including student entrepreneurship . Through interesting content And strategy creative delivery , social media capable build identity brand in a way wide . Besides that , the involvement of influencers as party the third one has influence big on social media can strengthen Power pull And credibility brand in the eyes Consumer.Research This use approach quantitative with method survey And technique Partial Least Square (PLS) analysis . Respondent in study This is student active running effort . Results study show that social media and influencers in general simultaneous influential positive And significant to business branding enhancement students . Social media play a role as channel main in expand range brand , while influencers help create connectedness emotional between brand And Consumers.Findings This show importance synergy between social media And strategy collaborative with influencers in build image strong brand . Research This give implications practical for student businessman in to design strategy effective digital marketing , as well as become contribution academic in enrich literature digital marketing based community campus.